2011
DOI: 10.1210/en.2010-1227
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Regulation of P-Glycoprotein in the Developing Blood-Brain Barrier

Abstract: The early fetal brain is susceptible to teratogens in the maternal circulation, because brain microvessel expression of drug efflux transporter, P-glycoprotein (P-gp), is very low. However, there is a dramatic up-regulation of brain microvessel P-gp in late gestation. This study investigated the role of cortisol and dexamethasone in this up-regulation of fetal brain microvessel P-gp expression. Primary brain endothelial cell (BEC) cultures derived from gestational d (GD)40, GD50, GD65 (term, ∼68 d) and postnat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(84 citation statements)
references
References 54 publications
7
77
0
Order By: Relevance
“…Thus, the increased sensitivity to opioids in newborn infants compared to older infants may be attributable, at least in part, to the low expression of P-gp at birth and thereby allowing opioids to concentrate in the CNS. P-gp immunoreactivity was detected in microvessels of the cortex as early as GA 20 wk suggesting that P-gp plays an important role in neuroprotection during fetal brain development, as has previously been shown in animal models (28). Previous studies in the human fetal brain detected P-gp in brain microvessels at crown-rump lengths corresponding to GA 17-24 wk, serving as an early marker of BBB development (26,27,29).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Thus, the increased sensitivity to opioids in newborn infants compared to older infants may be attributable, at least in part, to the low expression of P-gp at birth and thereby allowing opioids to concentrate in the CNS. P-gp immunoreactivity was detected in microvessels of the cortex as early as GA 20 wk suggesting that P-gp plays an important role in neuroprotection during fetal brain development, as has previously been shown in animal models (28). Previous studies in the human fetal brain detected P-gp in brain microvessels at crown-rump lengths corresponding to GA 17-24 wk, serving as an early marker of BBB development (26,27,29).…”
Section: Resultssupporting
confidence: 52%
“…Specifically, cyclosporine A accumulation within the brain was the highest in newborn mice and decreased with increasing postnatal P-gp expression (33). A study in guinea pig brain, which has a brain growth pattern that resembles human fetal development, showed that the expression of P-gp protein in the brain microvessels increases with advancing age (28,34). Hence, premature and full-term neonates may be at risk for CNS drug toxicity due to the limited BBB P-gp expression in the brain microvessels.…”
Section: Resultsmentioning
confidence: 99%
“…However, Demeule et al [38] and Iqbal et al [39] have independently demonstrated that the expression of P-gp is up-regulated by steroids and other hormones whose activity may change during aging. Whether endogenous and/or exogenous (feed) hormones affect ontogenic P-gp expression in chickens needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for such variability is that the ABCB1 gene is polymorphic, and two of its single-nucleotide polymorphisms (SNPs), rs1128503 and rs1045642, may modify the final protein conformation, compromising its membrane stability and substrate recognition 7,8. Finally, it has been reported that the ABCB1 expression may also be modulated by plasma aldosterone9 or cortisol,10 as well as by dietary salt and dehydration 9…”
Section: Introductionmentioning
confidence: 99%